Publication Trends of Research on Gallbladder Cancer During 2001–2021: A 20-Year Bibliometric Analysis - Sun, Wentao; Wan, Wenze; Gao, Zhihui; Suo, Tao; Shen, Sheng; Liu, Houbao (Frontiers in Oncology, 2022)
Gallbladder cancer (GBC) is one of the lethal cancers with an extremely poor prognosis. In recent 20 years, research on GBC has developed quickly. Here we aim to perform a systematical bibliometric analysis on the current foci and status of GBC research. This study analyzes trends in GBC research and compares contributions from different countries and regions, institutions and authors. All publications about GBC research from 2001 to 2021 in the Web of Science Core Collection (WOSCC) database were collected. Microsoft Excel 2010 and GraphPad Prism 9 were used to analyze publication data and publication trends. VOSviewer 1.6.17 was adapted to generate a visual network of keywords in surgical training research. A total of 3323 publications were included. China was the most productive country and contributed the highest number of publications (n=900, 27.08%). Shanghai Jiaotong University and Roa JC were the most productive institution and authors, contributing 215 and 89 publications, respectively. Keywords were classified into 5 clusters, which were the major topics. The main clusters of GBC are related to surgery therapy, mechanism research-related study, and non-surgery therapy. While migration is the current hotspot of GBC research. The scientific progression of GBC research over the past two decades was comprehensively analyzed by this bibliometric study. Finding deeper mechanisms in the migration of GBC cells, new biomarkers and highly effective nomograms will be the major problems and directions in the future.